Assessing the performance of Islamic banks comprising financial and non-financial performance by using multi-criteria decision analysis (MCDA) / Nurul Hanin Izzat Sanin and Nurul Fathiyah Kamarul Bahrin - Sanin, Nurul Hanin Izzat; Kamarul Bahrin, Nurul Fathiyah (2020)
The aim of this study is to assess financial and non-financial performance of Islamic banks in Malaysia. The financial and non-financial performances are analysed base on CAMEL ratings and Maqasid Sharia elements respectively. Therefore, a qualitative study had been applied in order to gain information from experts and high-rank managers who have working experiences. All the information was gained from the experts and high-rank managers’ minds who have experience and are qualified bankers. Pairwise comparison questionnaires were designed and distributed among them who are from 11 local Islamic banks by using purposive sampling technique. The data was extracted from pairwise comparison questionnaires and all the criteria and alternative elements were weighted by using Analytic Hierarchy Process (AHP). Multi-Criteria Decision Analysis (MCDA) technique was employed to rank the level of criteria. Hence, based on the findings, liquidity and preservation of faith show the highest rank which reflect to be the most important criteria in assessing financial and non-financial performance respectively. Thus, the pivot findings of this study give allusion for future researchers, regulator, investors as well as bankers to plan, design and improvise their decision analysis based on current financial and non-financial performance of Islamic banks.